Effects of Anaerobic Fermentation on Black Garlic Extract by Lactobacillus: Changes in Flavor and Functional Components - Ma, Li; Zhao, Chengying; Chen, Jifeng; Zheng, Jinkai (Frontiers in Nutrition, 2021)
The purpose of this study is to investigate the potential application of probiotics in the development of novel functional foods based on black garlic. The single-factor analysis (extraction temperatures, solid¬-to-liquid ratios, and extraction times) and the response surface methodology were firstly used to optimize hot water extraction of soluble solids from black garlic. The optimal extraction conditions were temperature 99.96 oC, solid-to-liquid ratio 1:4.38 g/mL, and extracting 2.72 h. The effects of Lactobacillus (Lactobacillus plantarum, Lactobacillus rhamnosus and co-culture of them) fermentation on physicochemical properties of black garlic extract broth were studied for the first time. Artificial and electronic sensory evaluations demonstrated that fermentation significantly influenced the sensory characteristics. The variations of metabolites in different broth samples (S1, unfermented; S2, 1 day fermentation by L. plantarum; S3, 2 days fermentation by L. rhamnosus; S4, 1 day fermentation by co-cultured Lactobacillus) were further investigated by gas chromatography-mass spectrometry and liquid chromatography-mass spectrometry/ mass spectrometry analysis. As a result, Lactobacillus fermentation significantly reduced the pH, increased contents of the total acid, amino nitrogen, total polyphenol and total flavonoid, and reduced the content of 5-hydroxymethylfurfural (a carcinogenic component) by 25.10–40.81% in the black garlic extract. The contents of several components with unpleasant baking flavours (e.g., furfural, 2-acetylfuran, and 5-methyl furfural) were reduced, whereas the contents of components with green grass, floral, and fruit aromas were increased. More importantly, the contents of several functional components including lactic acid, Gly-Pro-Glu, sorbose, and α-CEHC (3,4-dihydro-6-hydroxy-2,5,7,8-tetramethyl-2H-1-benzopyran-2-propanoic acid) were increased after Lactobacillus fermentation. The results demonstrated the potential of probiotic fermentation to improve the quality of black garlic. This work will provide insight into the strategic design of novel black garlic products and facilitate the application of black garlic in functional foods.